2016
DOI: 10.1590/0104-1428.2215
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das propriedades da blenda de poli(3-hidroxibutirato)/quitosana após esterilização térmica ou radiolítica

Abstract: AesumoNesse trabalho foi desenvolvido filme de PHB/quitosana com aplicação promissora em embalagens de alimentos e medicamentos. Esses filmes foram preparados via casting solution e após esterilização térmica ou radiolítica suas propriedades foram avaliadas a partir da microscopia eletrônica de varredura, ensaio de tração, calorimetria exploratória diferencial e análise termogravimétrica. Foram constatadas alterações na morfologia dos filmes de PHB/quitosana após os processos de esterilização. As propriedades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…According to Le Tien and coauthors [54], whey proteins have the capacity to crystallize during heating in film preparation. Abdelwahab and coauthors [55] and Souza and coauthors [56] also reported the influence of chitosan on the morphological characteristics of films based on biopolymers, with similar results.…”
Section: Films Surface Microstructure Characterizationsupporting
confidence: 52%
“…According to Le Tien and coauthors [54], whey proteins have the capacity to crystallize during heating in film preparation. Abdelwahab and coauthors [55] and Souza and coauthors [56] also reported the influence of chitosan on the morphological characteristics of films based on biopolymers, with similar results.…”
Section: Films Surface Microstructure Characterizationsupporting
confidence: 52%
“…This combination can be an option to reduce the demand for degradable packaging Polyhydroxybutyrate (PHB) is a well know biodegradable polymer used worldwide due to its crystalline structure, superior characteristics of aroma barrier, and water vapor permeability [9] . PHB is a thermoplastic polymer obtained from renewable natural sources that shown characteristics of biodegradability, biocompatibility, UV resistance and properties similar to the synthetic polypropylene [12][13][14] . However, the high crystallinity of PHB makes it very rigid and brittle, limiting its applications [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional synthetic polymers are widely used in our society due to characteristics such as low density, low cost of production, and facility for molding, among others. Due to their chemical constitution, however, they have a low rate of degradation, leading to environmental problems [1][2][3] . An alternative to these materials are the polymeric materials constituted by poly (α-hydroxy acids), which are biodegraded by microorganisms in CO 2 , water, and cellular components among other materials [4,5] .…”
Section: Introductionmentioning
confidence: 99%